Jeffrey Gitomer$1 (Bs little red book of selling : 12.5 principles of sales greatness :s how to make sales forever - Gitomer, Jeffrey (Charlotte, Bard Press Austin, 2005)
If salespeople are worried about how to sell, Gitomer believes they are missing out on the more important aspect of sales: why people buy. This, he says, is "all that matters," and his latest book aims to demystify buying principles for salespeople.
Keywords: Selling; Business networks; Customer loyalty; Customer relations; Audiobooks